Isolation, Quarantine, Social Distancing and Mental Health - Direk Tecirli, Neşe; Ucuz, Gizem; Ozel, Fatih (The Bulletin of Legal Medicine, 2020)
The COVID-19 pandemic directly affected more than 4 million people worldwide and indirectly affects the entire world due to its social consequences. There are methods such as isolation, quarantine, restriction of social distance, which are accepted all over the world to prevent the spread of infectious diseases considered pandemic. These practices, which are rapidly implemented in the modern age may be resulted in the mental health problems that affects individuals and societies for a long time. In this article, it is aimed to review the effects of these pandemic control practices such as isolation, quarantine and social distance on people’s mental health. These practices lead to different emotional responses such as anxiety and depressive symptoms in people. Depending on the type of coping strategies used to deal with stress and the severity of stress, these practices may cause several mental disorders including anxiety disorders, depressive disorders and stress-related disorders in vulnerable individuals. Delirium is seen frequently in COVID-19 as it has worse prognosis in olders adults. People who lost their loved ones may face complicated griefs as the deaths occurs in isolated conditions. In addition, stigmatization, which has serious outcomes, is a dangerous situation that may ocur agains affected individuals in isolation or quarantine during this period. It is important to keep these practices as short as possible, to support the society socially and economically, to facilitate access to the health system and to expand the mental health services in order to overcome this process with minimal damage.